Significance of Hydrogen Evolution in the Carbon and Nitrogen Economy of Nodulated Cowpea - Rainbird, Ross M. (1983)
The carbon and nitrogen economies of a single cultivar of cowpea (Vigna unguiculata (L.) Walp.cv Caloona) nodulated with either a high H(2)-evolving strain (176A27) or a low H(2)-evolving strain (CB756) of Rhizobium were compared. The two symbioses did not differ in total dry matter production, seed yield, nitrogen fixed, the spectrum of nitrogenous solutes produced by nodules for export, or the partitioning of net photosynthate within the plant throughout the growth cycle. Detailed examination of the carbon and nitrogen economy of the nodules, however, showed a significant difference between the symbioses. Nodules formed with CB756 lost less CO(2) in respiration compared to the higher H(2)-evolving symbioses and this could have been largely responsible for a 36% better economy of carbon use in CB756 nodules during the period of maximum H(2) evolution (48-76 days) and over the whole growth period (20-90 days), a 16% economy. In terms of overall net photosynthate generated by the plant, these economies were equivalent to 5% and 2% of the carbon utilized in the two periods, respectively. From the differences in H(2) evolution and CO(2) production by nodules of the two symbioses, the cost of H(2) evolution was found to be 3.83±0.6 millimoles CO(2)/millimoles H(2) for plants grown in sand culture and 1.69 ± 0.48 millimoles CO(2)/millimoles H(2) for those in water culture. In both symbioses, the ratio of H(2) evolution to N(2) fixed varied markedly during ontogeny, indicating a significant variation in the relative efficiency and thus metabolic cost of N(2) fixation at different stages during development.